(3NUGFU feh GdWad heQGYGJgG aj GdJQHjI GdESdGejI (B/s - (3GdTGT, gOGjI Gddg CMeOs ((3eUQ (B:s (3OGQ GdSdGe,s, 2020)
(3gPG GdcJGH jLeY Hjf GdCUGdI hGdeYGUQI, hjYjf GdBHGA hGdeYdejf Ydi eYQaI NUGFU feh CWaGdge hJdGePJge, hjeOge HGdSHd GdYedjI deQGYGJgG, dJSgd Ydjge GdJQHjI Ohf YbHGJ Ch eTcdGJ, hdcj jSJKeQhG aj GdLjd GdhGYO NjQ GSJKeGQ(B. (3hbO CHOYJ GdcGJHI Mjf CKHJJ Cf GdJQHjI GdESdGejI GdJj CHgQJ GdeacQjf Ydi eQ GdYUhQ GYJfJ HLhGfH JQHjI GdWad LSOG hYbdG hQhMG, hCfJLJ CLjGd GdMVGQI GdESdGejI GdPjf bOehG ddYGde JQHjI hMVGQI aQjOI de JbOegG ZjQgG ef GdCee(B.s
Keywords: (3GdCWaGds -- (3JQHjI ESdGejIs; (3GdCWaGd aj GdESdGes; (3GdCWaGds -- (3fehs